WITHDRAWAL: Molluscicidal activities of Tetrapleura tetraptera fruit extract, Aridanin and their particulate formulations on adult and newly hatched Biomphalaria glabrata snails - Ganiyu Akinniyi; Funmilola Fisusi; Bamigboye Taiwo (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2019)
Withdrawal Notice: This article is withdrawn at the authors’ request.